PSXIII-32 Effects of rumen-protected niacin on dry mater intake, rumination, and milk production in multiparous Holstein dairy cow during transition period. (5th December 2019) - Gaowa, Naren; Wang, Erdan; Li, Shengli; Cao, Zhijun; Wang, Yachun; Zhang, Jun; Wang, Yajing
Abstract: The dairy cows decrease dry mater intake (DMI) before calving and are frequently in negative energy balance after calving. The objective of this study was to investigate the effect of rumen-protected niacin (NA) on DMI, rumination, and milk production in multiparous Holstein dairy cows during transition period. Eighteen multiparous Holstein dairy cows were allocated into 3 groups: (1) control diet (Con; n = 6), not supplemented with NA, (2) supplemented diet 1 (NA1; supplemented with 20 g NA/cow daily, n = 6), and (3) supplemented diet 2 (NA2; supplemented with 40 g NA/cow daily, n = 6). Experimental stage was from 49 d before calving until 21 d after calving. Daily TMR intake was monitored by Roughage Intake Control System, and daily rumination time was monitored by Hr-Tag rumination monitoring system and milk yield was recorded every day after calving. Blood samples were collected on d -49, -35, -21, -14, -7, 1, 3, 7, 14, 21, and 28 relative to parturition for quantifying concentrations of neuropeptide Y (NPY) and orexin A (OXA). The 20 g/day NA feeding increased DMI during transition period (P < 0.05). The concentrations of NPY and OXA, which are the intake related hormones, were significant higher in NA1 than the other two groups in the first two weeks after calving (P < 0.05). Moreover, the daily rumination time in NA1 was significantly higher than the control group from two weeks before calving to the first week after calving (P < 0.01). The 20 g/day NA feeding significantly increased milk yield (P < 0.05) compared to control group in early lactation. Overall, our study demonstrated that 20 g/day NA feeding could improve DMI and production in fresh cows, while those improvements were not detected with 40 g/day NA feeding.